Evaluation of the distribution and progression of intraluminal thrombus in abdominal aortic aneurysms using high‐resolution MRI. Issue 3 (29th January 2019) - Zhu, Chengcheng; Leach, Joseph R.; Tian, Bing; Cao, Lizhen; Wen, Zhaoying; Wang, Yan; Liu, Xinke; Liu, Qi; Lu, Jianping; Saloner, David; Hope, Michael D.
Abstract : Background: Intraluminal thrombus (ILT) signal intensity on MRI has been studied as a potential marker of abdominal aortic aneurysm (AAA) progression. Purpose: 1) To characterize the relationship between ILT signal intensity and AAA diameter; 2) to evaluate ILT change over time; and 3) to assess the relationship between ILT features and AAA growth. Study Type: Prospective. Subjects: Eighty AAA patients were imaged, and a subset ( n  = 41) were followed with repeated MRI for 16 ± 9 months. Field Strength/Sequence: 3D black‐blood fast‐spin‐echo sequence at 3 T. Assessment: ILT was designated as "bright" if the signal was greater than 1.2 times that of adjacent psoas muscle. AAAs were divided into three groups based on ILT: Type 1: bright ILT; Type 2: isointense ILT; Type 3: no ILT. During follow‐up, an active ILT change was defined as new ILT formation or an increase in ILT signal intensity to bright; stable ILT was defined as no change in ILT type or ILT became isointense from bright previously. Statistical Tests: Shapiro–Wilk test; Mann–Whitney U ‐test; Fisher's exact test; Kruskal‐Wallis test; Spearman's r ; intraclass correlation coefficient (ICC), Cohen's kappa. Results: AAAs with Type 1 ILT were larger than those with Types 2 and 3 ILT (5.1 ± 1.1 cm, 4.4 ± 0.9 cm, 4.2 ± 0.8 cm, P  = 0.008). The growth rate of AAAs with Type 1 ILT was significantly greater than that of AAAs with Types 2 and 3 ILT (2.6 ± 2.5, 0.6 ± 1.3, 1.5 ± 0.6 mm/year, P  = 0.01). During follow‐up, AAAs with active ILT changes had a 3‐fold increased growth rate compared with AAAs with stable ILT (3.6 ± 3.0 mm/year vs. 1.2 ± 1.5 mm/year, P  = 0.008). Data Conclusion: AAAs with bright ILT are larger in diameter and grow faster. Active ILT change is associated with faster AAA growth. Black‐blood MRI can characterize ILT features and monitor their change over time, which may provide new insights into AAA risk assessment. Level of Evidence: 2 Technical Efficacy Stage: 5 J. Magn. Reson. Imaging 2019;50:994–1001.